The Culture of Conflict Resolution and its Influence on Employee Retention: A Study of Russian Companies - J. P. Bayer (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
Purpose — The purpose of this paper is a pilot study of e-communications in three Russian firms to assess the culture of conflict resolution and the impact of strategies on employee retention at these firms. Design/methodology/approach — Qualitative and quantitative research through a questionnaire and observation method to confirm the results. We use questionnaires by spontaneous sampling with quota elements; employees of the three selected firms have an equal chance of getting into an anonymous sample. Findings — The culture of conflict in any organization should include professional mediation (fulfilled either by professional instructor or by a specially trained HR-specialist). All members of the organizational “family” should be informed that dealing with conflict and solving it is much better and productive than hiding and suppressing it.Research limitations/implications — The paper shows the first results of the conflict study. It shows obvious drawbacks of contemporary empirical conflict solving. Further research should explore the effects of the recommendations we made and their fulfillment.Originality/value — The article assesses the main conflict triggers in Russian organizations of various sizes. It also reveals the key assumptions that both workers and employers have that prevent them from effectively resolving conflicts. Based on empirical results, we have developed practical recommendations on conflicts that will be useful not only for managing the organizations we have studied but also for those who have ever encountered a conflict at work.